Fuzzy Delphi Method Application Towards Usability Evaluation of Problem Solving Framework: Application in Education - Siti Khadijah Anis; Alias Masek (Indonesian Journal of Educational Research and Technology, 2024)
Non-digital games are tools that can help children build and improve problem-solving skills. Children need to solve problems using analogies from one situation to another, following the correct steps. To improve these skills, teachers play a role in guiding children so that these skills can be enhanced along with their age and developmental stage. However, the application of problem-solving skills in learning activities has become a challenge for teachers to implement because there are no specific reference sources that can be used as a guide. This is also supported by the findings of a needs analysis where there is a need to develop a problem-solving framework that focuses on problem-solving steps using non-digital games. The problem-solving framework has been developed and needs to be evaluated for its usability in the usability evaluation phase using the Fuzzy Delphi Method. It aims to measure the usability and suitability of the non-digital game-based problem-solving framework that has been developed in the design and development phase. 25 preschool teachers were selected as experts to provide feedback through a questionnaire. The findings show that all experts in this phase agree that all main components, elements in the main components, and the priority flow for each element of the problem-solving framework have achieved an appropriate status and show a high consensus on the usability of the problem-solving framework that has been developed. Therefore, the problem-solving framework can be used by preschool teachers as a specific guide in implementing problem-solving activities using non-digital game.